PRECLINICAL EVALUATION OF POLYHERBAL FORMULATION FOR FEMALE SEXUAL DYSFUNCTION - DIPTI KASPATE,; A.R. ZIYAURRAHMAN,; TINA SALDANHA,; POOJA KALE, (International Journal of Pharma and Bio Sciences, 2015)
In the present study, Aphrodisiac activity of Polyherbal Formulation made from hydroalcoholic extract of Chlorophytum borivilianum, ethanolic extract of Tribulus terrestris and hydroalcoholic extract of Withania somnifera in 1:1:1 proportion was investigated in tubal ligated female rats by using Automated runway methodology, Mating behaviour in Copulatory Arena and L-NAME (Nω-Nitro-L arginine methyl ester HCL) induced female sexual dysfunction models with doses 250, 500 and 750 mg/kg, (p.o). In automated runway methodology and mating behaviour models dosing was done for 21 days and readings were taken on 11th and 21st day of treatment days. After end of these two models supportive studies were also done viz. serum estradiol study and effect of Polyherbal Formulation on eNOS expression of vaginal tissue by Reverse Transcriptase Polymerase Chain Reaction. While for L-NAME induced female sexual dysfunction model dosing was done for 28 days and readings were taken on 11th and 28th day of treatment days. At the end of this study, supportive studies were also done viz. serum estradiol study and histology of vagina, uterine horn, ovary. All the results showed that Polyherbal Formulation has significant aphrodisiac activity and explore some of the possible mechanism by which these plants may be effective in female sexual dysfunction. In the study of serum estradiol hormone and Reverse Transcriptase Polymerase Chain Reaction method 250mg/kg dose of each individual herb of Polyherbal Formulation was also tested and compared against 250mg/kg dose of Polyherbal Formulation which concluded that these herbs have a synergistic effect in combination and dose reduction is possible.